Drug delivery to the lymphatic system: The road less travelled - Annamalai Rama, Induja Govindan, Anjana A. Kailas, Thamizharasan Annadurai, Shaila Angela Lewis, Sreedhara Ranganath Pai, Anup Naha (Journal of Applied Pharmaceutical Science, 2024)
This article explores the physiological and pharmaceutical barriers influencing drug bioavailability for the oral route of administration, as well as the different pharmaceutical technologies and drug delivery systems that have been explored to enhance oral drug absorption. The manuscript also examines the advantages and limitations of drug delivery to the lymphatic system and presents the future directions and challenges associated with this approach. Specifically, the manuscript highlights that drug delivery to the lymphatic system holds promise for improving drug bioavailability and efficacy. It emphasizes the advantages of delivering drugs to the lymphatic system, including enhanced drug solubility, stability, lymphatic transport, and the ability to target specific lymphatic vessels. The manuscript further explores future directions in this field, such as developing novel formulations, targeting specific lymphatic vessels, and combination therapy. However, the manuscript acknowledges significant challenges for the clinical translation of lymphatic drug delivery approaches. Regulatory hurdles, safety concerns, and cost and scalability are vital obstacles to address. The manuscript concludes by emphasizing the importance of addressing these challenges and fostering further research and collaboration to optimize the clinical translation of lymphatic drug delivery.
Keywords: Drug delivery, lymphatic system, novel formulations, targeted therapy, combination therapy